Design And Build Web-Base Application Library Management System - Tengfei, Li; Jie, Zhang; Fahmi, Hasanul (President University, 2024)
At present, most of China's higher education institutions have completed the computerization of library management, and library management is more scientific and efficient. However, many university library management systems have some problems, such as outdated functions, aging systems and unstable operation. In this paper, the authors designed a library management system. Under the Javaweb environment, the whole system is built using SpringMVC framework, MySQL database as the data storage support of the system, Windows 10 as the operating system, and Tomcat 8.0 as the web server. With the help of this technology stack, the problem of unstable operation of the previous system is solved, and a more efficient and stable library management information system is constructed, which not only reduces the workload of librarians, but also provides students with a more convenient book borrowing and lending experience, so that the library can play the most useful role in the campus life.